A study of echocardiographic changes in patients of thalassemia major - Chanpura, Vaishali R.; Modi, Daxay (International Journal of Contemporary Pediatrics, 2019)
Background: Thalassemia major is a chronic hematological disorder. Regular blood transfusion is the only modality of long-term survival for these patients. This leads to iron overload, the heart being the most severely affected organ. The gold standard for detecting myocardial iron deposition is cardiac MRI. However, very few patients can afford this investigation. Hence, authors carried out this study to find out whether early iron overload can be detected by echocardiography which is a simple and less expensive tool. The objective of this study was to document echocardiographic changes of cardiac iron overload in patients of thalassemia major even before appearance of symptoms. Methods: A comparative cohort study conducted from January 2018 to October 2018 in the Department of Paediatrics of SSG Hospital, and Government Medical College, Vadodara. The case group consisted of 35 patients of Thalassemia major. 35 age and sex matched normal children were selected as controls. Relevant blood investigations were performed in cases. 2-Dimensional M-Mode Echocardiography was performed in both patients and controls. Thalassemia major patients were compared to normal healthy children for various parameters in echocardiography indicating the systolic and diastolic function. Proportion and percentage were calculated for descriptive analysis. Independent t-Test was applied between two groups to find out significance level. Results: For all parameters except End systolic volume and fractional shortening, p values were less than 0.05 which is significant. 85% (30/35) had increase in interventricular septal dimensions (IVSD), 97%(34/35) had increase in posterior wall dimensions (PWD), 82%(29/35) had increased left ventricular internal diameter diastole(LVIDD), 88%(31/35) had increased left ventricular internal diameter systole (LVIDS), 80%(28/35) had increased E/A RATIO .Ejection fraction was affected in 77%(27/35).This shows that patients of thalassemia major have significant cardiac dysfunction; possibly because of cardiac iron overload. Conclusions: Echocardiography is an effective tool for screening cardiac iron overload in patients of thalassemia major and should be done periodically in all patients.